THE ROLE OF DIGITAL TAXATION IN DIGITAL TAX AWARENESS THROUGH DIGITAL TAX LITERACY: EVIDENCE FROM INDONESIA'S GENERATION Z - Rissa Anandita; Raden Roro Diana Atika Ghozali; Naila Hanum; Gabrielle Selma Jonetta Silalah (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2025)
Generation Z, often called digital natives, has unique characteristics that influence how they perceive and fulfill tax obligations in the digital era. However, many young Indonesians are still unfamiliar with the concept of digital taxes applied to everyday online transactions. This study aims to examine the relationship between digital taxation and digital tax awareness, with digital tax literacy acting as a mediating variable among Generation Z in Indonesia. Using a quantitative research design, the study employed Partial Least Squares (PLS) analysis through the SmartPLS 3 application. The population consisted of Generation Z individuals in Indonesia, selected using purposive sampling, resulting in 301 respondents. Data were collected through a structured, closed-ended questionnaire. The results reveal four main findings. First, digital tax literacy positively influences digital tax awareness, showing that greater understanding leads to higher awareness. Second, digital taxation positively affects digital tax awareness, suggesting that implementing digital tax policies increases public understanding of tax compliance. Third, digital taxation strongly impacts digital tax literacy, emphasizing the role of tax systems in shaping knowledge of digital tax mechanisms. Lastly, digital tax literacy significantly mediates the relationship between digital taxation and digital tax awareness, highlighting its key role in strengthening the effectiveness of digital tax implementation among Generation Z in Indonesia.